PENINGKATAN PEMAHAMAN AKUNTANSI DASAR SEBAGAI BEKAL KEMANDIRIAN EKONOMI SISWA MA NW PESENG - Luh Utami; Widiya Pratiwi; Rini Yuliandari; Arjuna Arjuna (LPPM Institut Pendidikan Nusantara Global, 2026)
This community service activity aims to improve students' understanding of basic accounting as a foundation for economic independence at MA NW Peseng. The activity was carried out through socialization methods, material delivery, interactive discussions, and simple financial transaction recording practices. The target group was 30 MA NW Peseng students who still have limitations in understanding basic accounting concepts and simple financial management. The material provided included basic accounting concepts, transaction recording, income and expense reports, and the importance of financial management in everyday life. Evaluation was carried out through questionnaires before and after the activity. The results of the activity showed an increase in student understanding across all measured indicators. Understanding of basic accounting concepts increased from 50% to 85%, understanding of simple transaction recording increased from 45% to 80%, understanding of income and expense reports increased from 50% to 85%, and understanding of the importance of financial management increased from 50% to 90%. The average level of student understanding increased from 48.75% to 85%, or an increase of 36.25 percentage points. In addition, students showed high enthusiasm during the practice session. This activity has proven effective in increasing accounting literacy and financial management awareness of students as a provision to support economic independence from school age.